HBR's 10 must reads on teams - HBR (Boston Harvard Business Review Press, 2013)
If you read nothing else on building better teams, read these 10 articles. We?ve combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you assemble and steer teams that get results.
Includes index.
Keywords: Teams in the workplace